Effect of water stress on seed germination and seedling growth in Oryza sativa L. - Takaki, M. [UNESP] (Institute of Experimental Botany, 1990)
The effect of water stress induced by application of polyethylene glycol 6000 during seed germination and seedling growth of Oryza sativa L. cv. IAC 165 was analysed. The seed germination was inhibited by the decrease in the water potential of the medium, the inhibition being greater under white light than under continuous darkness. When the seedling was submitted to water stress (-0.51 MPa) white light inhibited growth of root, coleoptile-and leaf, while under no stress conditions white light caused increase in growth of root and leaf and only inhibition of coleoptile growth. © 1990 Kluwer Academic Publishers.